Improving intergroup relations - Stephan, Walter G.; Stephan, Cookie White; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2001)
This book is intended both as supplementary reading for courses and as a practical guidebook for individuals and programmes interested in reducing prejudice and improving intergroup relations. It provides the only comprehensive review and compilation of techniques for roving intergroup relations.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Group relations training; Intergroup relations; Group relations training -- United States; Intergroup relations -- United States; Electronic books